A causal model on assertiveness, stress coping, and workplace environment: Factors affecting novice nurses' burnout. Issue 3 (23rd January 2021) - Suzuki, Eiko; Takayama, Yuko; Kinouchi, Chiaki; Asakura, Chihiro; Tatsuno, Hirotoshi; Machida, Takae; Yanahara, Hiroe; Kitajima, Hiroko; Miwa, Masae
Abstract: Aim: This study aimed to develop and test a causal model focused on assertiveness, stress coping, and workplace environment as factors affecting burnout among novice nurses. Design: Cross‐sectional study was conducted with novice nurses of 17 hospitals. Methods: The Novice Nurse Assertiveness Scale and the Japanese version of Maslach Burnout Inventory. Results: Data from 645 female novice nurses were analysed. The mean age, Novice Nurse Assertiveness Scale and Maslach Burnout Inventory were 22.6 ± 3.0, 67.4 ± 10.3 and 13.7 ± 2.5. For the final model, the study adopted a model that includes indirect influences; inappropriate assertiveness and inappropriate coping affected the dissatisfaction with the job and then affected the burnout. The goodness of fit index was GFI = 0.94, AGFI = 0.91, RMSEA = 0.66, and R 2 was .86. The findings validated this as a causal model of assertiveness, stress coping, and the work environment as factors affecting burnout for novice nurses.